Development, implementation and evaluation of school-based smoking prevention education program among non-smoking adolescents - Siti Hajar binti Mohamed Zain (Kulliyyah of Nursing, International Islamic University Malaysia, 2018)
Preventing smoking among adolescents is critical to end the epidemic of smoking in Malaysia. Despite the implementation of several smoking prevention programs, the prevalence of adolescent smoking and experimenting with tobacco in Malaysia is still increasing. Therefore, the purpose of this quasi-experimental study was to evaluate the effectiveness of Smoking Prevention Education Programs (SPEP) in preventing the smoking initiation among non-smoker adolescents based on their smoking status on follow-up and smoking intention, which includes; attitude, subjective norms, and perceived behavioural control as described by the Theory of Planned Behaviour. A total of 140 Primary five students (non- smokers) were involved in this study. Four schools in Kuantan district were randomly assigned to intervention and control groups. The intervention schools received a lecture on the hazards of smoking and SPEP intervention whereas the control schools received just a lecture on the hazards of smoking. The questionnaires and exhale carbon monoxide levels were first assessed at baseline and then again after three months. The findings of this study showed that after three months, the percentage of never smoker remained 100% in the intervention group, compared to the control group, and 2.9% of participants reported to have smoked in past seven days. Furthermore, the results indicated that the mean score of attitude, subjective norm, and smoking intention of the intervention group improved significantly after the SPEP intervention. In addition, the findings indicate that being a male (b= 0.494, p=<0.001), having friends who smoke (b= -0.82, p=0.023), and having positive attitude toward smoking (b= -0.669, p= <0.001) were significant factors for smoking intention among adolescents. The current study demonstrated that, in short-term, the SPEP intervention was effective in preventing smoking intention and smoking initiation, and it can be integrated as a part of the school curriculum. Additionally, the study has identified valuable information to improve existing smoking prevention programmes through combining the social influence and social competence approach. Further studies are recommended to assess the long-term effectiveness of SPEP intervention. KEYWORS: Adolescents, Non- smoker, Smoking Prevention Education Program.